Surveillance prostate biopsy utilizing piflufolastat F 18-PET/CT targeting in the intact prostate – A case report - Tim Grossman; Kathryn A. Morton (Urology Case Reports, 2023)
75-year-old patient with cochlear implant diagnosed with very low risk prostate cancer (PSA 6.44 ng/mL, and Grade Group 1 (left apical core)) managed on Active Surveillance (AS). After four years monitoring on AS, PSA was observed to increase to 10.84 and patient was reevaluated for disease progression. Due to cochlear implant, multiparametric MRI was not an imaging option and patient was referred for piflufolastat F 18-PET/CT. In addition to previously identified left sided lesion, tracer uptake was observed within the posterior transition and peripheral zone of the right lobe of the prostate, which ultimately confirmed disease progression on targeted biopsy.